ANALISIS KEPEMIMPINAN KEPALA RUANGAN DALAM PENERAPAN BUDAYA KESELAMATAN PASIEN DI RUMAH SAKIT JIWA DAERAH Dr. AMINO GONDOHUTOMO SEMARANG - Nurul Ayu Ningsih; Sudiro Sudiro; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2017)
The head room UPIP in Dr. Amino Gondohutomo Semarang Local Psychiatric Hospital lacks in evocative process, make others do, in becoming a role model, and in giving leadership encouragement related to WalkRounds, safety champion, and briefing staff. There are 10 steps taken to support the patient safety culture with the approach of the Institute for Healthcare Improvement. The objective of this study is to analyze the head of service’s leadership in the implementation of patient safety. The method used in this study is qualitative method. The informants were eight people consisting of main and triangulation informant, the deputy director, the head of medical committee, the head of room service, secretary KPRS, and the four nurses. The result can be concluded based on the facts such as has not yet formed a champion safety in every units, does not give a routine encouragement to the staff, does not give enough examples of patient safety to the staff during briefing time, and lack of building a reporting culture, and learning culture. Suggestion from the research to the hospital is to provide information regarding the number of occurrences in space UPIP for all hospital employees and socialization to nurse the importance of reporting the incident, form a safety champion in each unit as a driver and a conduit of information issues of patient safety, encourage a routine from every month to every day to the staff, provides examples of behavior-related directives safety is supported by a team KPRS periodically/regularly, socialization to all nurses to not be afraid to report, and pay attention to the cases of patients in the room UPIP as learning such as overseeing special patients who often flee and patients often fall.